Stem Cell Repair for Cardiac Muscle Regeneration: A Review of the Literature - Georgiana Farrugia; Rena Balzan (University Library System, University of Pittsburgh, 2016)
The notion that the human adult heart is a quiescent organ incapable of self-regeneration has been successfully challenged. It is now evident that the heart possesses a significant ability for repair and regeneration. Stem cells of endogenous cardiac origin are currently considered to possess the greatest ability to differentiate into cardiomyocytes. The major types of cardiac stem cells that show a promising potential to replace damaged cardiomyocytes include C-KIT positive (C-KIT+) cardiac progenitor cells, cardiosphere-derived progenitor cells, islet-1 (Isl1+) cardiac progenitor cells, side-population cardiac progenitor cells, epicardium-derived progenitor cells and stem cell antigen-1 (SCA1+) cardiac progenitor cells. Moreover, stem cells of extra-cardiac origin are also thought to restore contractility and vascularization of the myocardium. These include skeletal myoblasts, bone marrow mononuclear cells, mesenchymal stem cells, endothelial progenitor cells as well as embryonic stem cells. The need for further investigation on cardiac stem cell therapeutic strategies still remains.